Antimicrobial Peptides As Biologic and Immunotherapeutic Agents against Cancer: A Comprehensive Overview - Roudi, Raheleh; Syn, Nicholas L.; Roudbary, Maryam (Frontiers in Immunology, 2017)
Antimicrobial peptides (AMPs) are a pervasive and evolutionarily ancient component of innate host defense which is present in virtually all classes of life. In recent years, evidence has accumulated that parallel or de novo mechanisms by which AMPs curb infectious pathologies are also effective at restraining cancer cell proliferation and dissemination, and have consequently stimulated significant interest in their deployment as novel biologic and immunotherapeutic agents against human malignancies. In this review, we explicate the biochemical underpinnings of their tumor-selectivity, and discuss results of recent clinical trials (outside of oncologic indications) which substantiate their safety and tolerability profiles. Next, we present evidence for their preclinical antitumor activity, systematically organized by the major and minor classes of natural AMPs. Finally, we discuss the barriers to their clinical implementation and envision directions for further development.